Faktor-faktor yang Menentukan Keputusan Konsumen dalam Pembelian dan Konsumsi Smoothie Bowl di Restoran Nalu Bowls Seminyak - MALAU, RUTH MADEARNI; WINDIA, I WAYAN; AGUNG, I DEWA GEDE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.8, No.3, Juli 2019, 2019)
Factors that Determine Consumer Decisions in Buying and Consuming Smoothie Bowls at Nalu Bowls Restaurant in Seminyak Trade competition, especially in the culinary/food sector, is very strict, requiring all business owners, espesially restaurant business, to be more courageous in taking innovations. The purpose of these innovations is sales, and can influence the decision of consumers to buy a product. Restaurant Nalu Bowls is a business venture that is engaged in the culinary field and is one of the restaurant innovations that has its own picture to meet consumer needs, namely a healthy food menu that it offers. In the most famous Nalu Bowls, research in needed. The purpose of this study were (1) to analyze the characteristics of consumers in Nalu Bowl Restaurant, (2) Analyze the decision process in the purchase of a smoothie bowl at Nalu Bowls Restaurant, (3) Analyze the factors that influence consumer decisions to buy products in Nalu Bowls Restaurant.The results of the study show that several stages of the restaurant of Nalu Bowls Restaurant consumers before making a purchase, namely needs recognition, information search, alternative evaluation, purchase and post-purchase. Factors affecting consumers in deciding the purchase of smoothie bowls consist of three factors, namely product and supporting factors, service factors and restaurant identity, and food appearance factors. The advice that can be given is that Nalu Bowls Restaurant should be able to give a good impression to its customers because by giving a good impression, it can bring the possibility of the consumer to provide good information to his friends about Nalu Bowls which has an impact on the increasing number of consumers visiting Nalu Bowls.